Konsep Belajar Ibnu Taymiyyah Dan Relevansinya Dengan Pendidikan Kontemporer - Nisa Ayanti; Nia Kurniawati; Ali Maulida (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
Contemporary Islamic education faces various challenges related to technological developments, globalization, moral crises, and the tendency toward a dichotomy in knowledge. Underthese circumstances, the educational thought of classical scholars has once again gained attention as a source of values and an educational paradigm relevant to the needs of the times. One figure who has made a significant contribution to the field of Islamic education is Ibn Taymiyyah. This study aims to analyze Ibn Taymiyyah’s concept of learning and examine its relevance to contemporary education. The study employs a literature review (library research) method with a descriptive qualitative approach. Data were obtained from the works of Ibn Taymiyyah and various scholarly articles discussing Islamic educational thought. The results of the study indicate that the concept of learning according to Ibn Taymiyyah is built upon the principle of tawhid, the integration of knowledge and action, the proportional development of reason, the cultivation of character, and the importance of experience in acquiring knowledge. These concepts have strong relevance to contemporary educational paradigms, particularly in strengthening character education, holistic learning, student-centered learning, the integration of knowledge, and the comprehensive development of students’ competencies. Ibn Taymiyyah’s thought can serve as a conceptual alternative in addressing the challenges of modern education without neglecting Islamic values.